PREVALENSI KEJADIAN ANOREKSIA PADA LANSIA - Chrisyen Damanik; Sumiati Sinaga; Maichel Alexander (ITKES Wiyata Husada Samarinda, 2017)
The prevalence of anorexia sufferers in the elderly will continue to increase due to the aging process which can be detrimental to quality of life, morbidity, and mortality. By using simple measurements through the anorexia questionnaire, it is known that the elderly who experience good and bad appetite. This study was to determine the prevalence of anorexia in the elderly at the Tresna Werdha Nirwana Social Home Puri Samarinda. This study is a cross-sectional measurement study that is descriptive in nature, random sampling with 80 respondents. The prevalence of anorexia from 80 respondents, mostly women 62.5% with the highest age of 45-59 years, showed that the risk of anorexia was 41.3% and those not at risk 58.8%. In the care of the elderly at social institutions so that they can provide material about anorexia so that they can reduce those that can harm the health of the elderly at the Tresna Werdha Nirwana Social Home Puri Samarinda